Influence of labour migration on the European integration of national financial systems - Кулай, Аліна Василівна; Kulaj, A. V. (Šiaulių universiteto Socialinių mokslų fakultetas, 2014)
In the article it is considered scientific and practical aspects of modern condition of migration processes in Ukraine and around the world, influence of labor migration on world labor market, economics and national financial system. It was revealed the essence of synergetic effect in conditions of international integration processes. For the purpose of intensification of labor migration for strengthening of national financial systems it was presented systematic improvement of institutional arrangement of migration environment in conditions of state–private partnership and it was also defined the ways of inter–state cooperation in the scope of labor migration management.
Вплив трудової міграції на євроінтеграціюнаціональних фінансових систем
Keywords: labor migration; institution environment; integration; convergence of migration policy; national financial systems